Usefulness of the Fullerton Test in Qualifying Patients with Chronic Obstructive Pulmonary Disease for Rehabilitation - Jan Szczegielniak; Anna Wdowiak; Katarzyna Bogacz; Jacek Luniewski (Lithuanian Sports University, 2020)
Adequate, individually based choice of training type and intensity is a prerequisite for physiotherapy of patients with COPD. The basic criteria for qualification include effort tolerance assessment by means of exercise test on cycloergometer or treadmill or 6-minute walk test and determining the degree of lung ventilation activity impairment, dyspnea level and patient's physical condition. The Fullerton test is an easy and time-effective tool allowing for effort tolerance and physical condition assessment in case of patients above the age of 60. The objective of this work was to assess the usefulness of the Fullerton test in qualifying patients with COPD for rehabilitation. Thirty two patients with diagnosed COPD were tested in the research. The group comprised in-patients treated in the MSWiA Hospital in Glucholazy between February 1 and May 10, 2011. All patients in the research were above 60 years of age, with median age of 68 ± 5.2. The patients were given pulmonary rehabilitation model A and B according to Szczegielniak. In the research, the results recorded in 6 trials of the Fullerton test were compared to the results of standard tests qualifying for pulmonary rehabilitation. For this purpose, a 10-point scale was created by the authors, which included parameters achieved in the Fullerton test allowing comparison of the results achieved in the Fullerton test and standard qualification procedure. The T-student test was used to assess the relationships between the tested parameters. Statistical significance level was established at p < 0.05. The analysis of research results showed that patients who scored higher on the scale were qualified for higher pulmonary rehabilitation models, which means they achieved higher results in qualification tests. The Fullerton test might be useful for the assessment of the results and progress of pulmonary rehabilitation process. Keywords: Fullerton test, effort tolerance assessment, pulmonary rehabilitation.